(untitled) (Bangladesh Pharmaceutical Journal, 2013)
Ibuprofen, a non-steroidal anti-inflammatory drug was formulated as microspheres by using Methocel K4M & Eudragit RSPO. These microspheres were prepared by emulsification solvent evaporation method to provide sustained action and to minimize local side effect of Ibuprofen by avoiding the drug release in the upper gastrointestinal tract. The prepared microspheres were subjected to various evaluation and in-vitro release studies. In-vitro drug release was studied in a paddle type dissolution apparatus (USP Type II Dissolution Apparatus) using Phosphate buffer (pH 7.4) as the dissolution medium at 37.5oC for 6 hours (paddle speed 50 RPM). The release mechanisms were explored and explained with Zero Order, First Order, Higuchi and Korsmeyer-Peppas equations. The correlation coefficients values of the trend lines of the graphs showed that the formulations best fit with Korsmeyer-Peppas release pattern. Microspheres morphology and chemical integrity were studied by a scanning electron microscope (SEM) and Fourier transforms infrared spectroscopy (FTIR) respectively. DOI: http://dx.doi.org/10.3329/bpj.v16i1.14489 Bangladesh Pharmaceutical Journal 16(1): 39-44, 2013